CORPORATE DEBTS AD CREDIT PERFORMANCE UNDER THE NEW MECHANISM OF REORGANIZATION OF THE RUSSIAN BANKS - S. A. Andryushin; V. K. Burlachkov; A. A. Rubinshtein (Russian Journal of Economics and Law, 2017)
Objective: to explore the dynamics and factors of formation of corporate debts, the characteristics of low credit activity of the Russian banks and regulation of liquidity deficit of enterprises under the new reorganization mechanism in the Russian banking sector.Methods: systematic approach to the cognition of economic phenomena, which allows to study them in their dynamic development, taking into account the influence of various environmental factors. The systematic approach determined selection of specific research methods: empirical, logical, comparative and statistical.Results: the article is devoted to the problems of declining credit activity of commercial banks under the conditions of economic activity revival, as well as to assessing the impact of the new reorganization mechanism on this process. It is shown that in the recent years the non-financial sector faces the trend of optimizing the corporate debts and the liquidity deficit, which reduced the demand for loans and, as a consequence, decreased the banks’ credit activity.To analyze the dynamics of deficit/surplus of liquidity in the corporate sector, a new classification of liquidity deficit/surplus levels was introduced. Based on the proposed classification, the risk factors were identified that influenced the dynamics of indebtedness in the corporate sector.The article also analyses the modern monetary mechanism of money supply in the economy and its transformation. It was determined that the main limitation of credit issuance by commercial banks is their capital, not the reserve multiplier. The new mechanism of credit institutions’ financial recovery and its impact on the banks’ credit activity was estimated. The conditions of liquidity deficiency reduction in the Russian companies were analyzed in the medium term.Scientific novelty: for the first time, on the basis of system analysis methods, the growth factors of the corporate debt load were identified, the peculiarities of low credit activity in the banking sector were investigated, as well as and the possibility to regulate the liquidity of Russian enterprises under the conditions of a new mechanism of the Russian banks’ reorganization. Practical significance: the main provisions and conclusions of the article can be used to modernize and clarify the target mandates, instruments, channels and mechanisms of the Bank of Russia monetary policy, which enable to increase the Russian banks’ credit activity and to reduce the corporate debts of enterprises to the maximum permissible level.